HUBUNGAN RENTANG UKURAN BUTIR TERHADAP BESARAN BATUAN - Siti Sarah Munifah; Siska Nuraidah; Siti Marya Darmawati; Selly Feranie (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2017)
Porous rock composed of solid material and pores. Rock quality can be determined by various aspects as porosity, specific surface area and permeability which are affected by the size of grain occupying space on the rock. Rock model was then done by random penetrable sphere packing method which represent the simplest form of rock. Porosity is the ability to reserve, meanwhile permeability is the ability to deliver fluids without wrecking the rock structure. Specific surface area is the ratio of surface area with material mass or volume. The greater the variety of grain used, the smaller the value of porosity and permeability are, because of the rock spaces occupied will be larger. Thus, the value of specific surface area will increase. Keywords: porous rock models, porosity, permeability, specific surface area